A rational tissue engineering strategy based on three-dimensional (3D) printing for extensive circumferential tracheal reconstruction. (December 2018) - Park, Jeong Hun; Park, Ju Young; Nam, Inn-Chul; Ahn, Minjun; Lee, Jae Yeon; Choi, Seok Hwa; Kim, Sung Won; Cho, Dong-Woo
Abstract: Extensive circumferential tracheal defects remain a major challenging problem in the field of tracheal reconstruction. In this study, a tissue-engineered tracheal graft based on three-dimensional (3D) printing was developed for extensive circumferential tracheal reconstruction. A native trachea-mimetic bellows scaffold, a framework for a tissue-engineered tracheal graft, was indirectly 3D printed and reinforced with ring-shaped bands made from medical grade silicone rubber. A tissue-engineered tracheal graft was then created by stratifying tracheal mucosa decellularized extracellular matrix (tmdECM) hydrogel on the luminal surface of the scaffold and transferring human inferior turbinate mesenchymal stromal cell (hTMSC) sheets onto the tmdECM hydrogel layer. The tissue-engineered tracheal graft with critical length was anastomosed end-to-end to the native trachea and complete re-epithelialization was achieved on the entire luminal surface within 2 months in a rabbit model with no post-operative complications. With this successful result, the present study reports the preliminary potential of the tissue-engineered tracheal graft as a rational tissue engineering strategy for extensive circumferential tracheal reconstruction.